Social Support, Flexible Resources, and Health Care Navigation - Gage-Bouchard, Elizabeth A. (Soc Sci Med, 2017)
Recent research has focused attention on the role of patients’ and clinicians’ cultural skills and values in generating inequalities in health care experiences. Yet, examination of how social structural factors shape people’s abilities to build, refine, and leverage strategies for navigating the health care system have received less attention. In this paper I place focus on one such social structural factor, social support, and examine how social support operates as a flexible resource that helps people navigate the health care system. Using the case of families navigating pediatric cancer care this study combines in-depth interviews with parents of pediatric cancer patients (N = 80), direct observation of clinical interactions between families and physicians (N = 73), and in-depth interviews with pediatric oncologists (N = 8). Findings show that physicians assess parental visibility in the hospital, medical vigilance, and adherence to their child’s treatment and use these judgments to shape clinical decision-making. Parents who had help from their personal networks had more agility in balancing competing demands, and this allowed parents to more effectively meet institutional expectations for appropriate parental involvement in the child’s health care. In this way, social support served as a flexible resource for some families that allowed parents to more quickly adapt to the demands of caring for a child with cancer, foster productive interpersonal relationships with health care providers, and play a more active role in their child’s health care.